DYNAMICAL EVOLUTION OF BINARY STAR CLUSTER FORMATION IN MILKY WAY AND LARGE MAGELLANIC CLOUD FROM FRACTAL MODEL - DARMA - NIM: 20317002 , RENDY
MIStIX survey showed that most of young star clusters (a few Myr) have clumpy structures. Observations and statistical studies also concluded that there are binary star clusters in Milky Way and Large Magellanic Cloud. Their typical ages are less than 25 Myr. Some mechanisms were proposed to explain the formation of binary star clusters. One of those mechanisms is related to the clumpy structure of star clusters, i.e. simultaneous formation which yields the primordial binary cluster. In my thesis project, I performed N-body simulation of the formation of primordial binary clusters with fractal distribution using AMUSE Framework. Three conditions were studied in this thesis project, i.e. isolated, including Milky Way potential, and including Large Magellanic Cloud potential. The identiﬁcations of binary star clusters at time 20 Myr dan 50 Myr were statistically done using K-Means and calculation of total energy. The results showed that the more clumpy the structure of star cluster, the more binary star cluster or multiple system can be formed at the early formation of star cluster (≤ 20 Myr). Gravitational interactions between them can trigger the merger processes which cause the decreasing number of binary star cluster from 20 Myr to 50 Myr. Generally, this process occurs in those three conditions. Beside that, in conditions where the Milky Way potential and Large Magellanic Cloud potential are included in the simulations, there is a lot of multiple systems survive at 20 Myr and it has important role on the increasing and decreasing number of binary star cluster within 50 Myr. From all of N-body simulations made in this thesis project, the implementation of fractal distribution on the formation of primordial binary cluster by simultaneous mechanism is apparently signiﬁcant. It can be seen generally from the binary fractions, which have range of 40%−80% at time 20 Myr and less than 60% at time 50 Myr.